Sunnatullah as a Basis for Interpretation of the Qur'an and Hadith About Covid-19 on Indonesian Social Media - Mukhamad Agus Zuhurul Fuqohak; Yuyun Affandi; Moh. Nor Ichwan (Jurnal Theologia, 2021)
Sunnatullah (Causality Law) as the basis of interpretation is intended to make its concept as a limitation (taqyîd) from the generality or absoluteness of the al-Qur'an and Hadith texts. For example, the texts that talk about the implementation of congregational prayers, Friday prayers, other worship suggestions related to the crowd, are restricted by the rules (sunnatullah) of social distancing taken from the understanding of other religious texts. The massive number of people who state they should not be afraid of Covid19 and should only fear Allah is evidence of the lack of use of the concept of sunnatullah as the basis for interpreting the Qur'an and Hadith. Qualitative research using field-library and ethnographic research methods find that it is necessary to understand religious texts coupled with an understanding of the social sciences and humanities, especially the concept of sunnatullah. This research is intended to contribute to proper comprehension in understanding the Qur'an and Hadith so that there will be no contradiction in its interpretation with social, economic, political and health realities.